Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Hasil Belajar Ipa Kelas 2 Sdn 16 Timbulun - Desmi, Desmi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this study was to improve science learning outcomes for grade 2 students of SDN 16 Timbulun, Tanjung Gadang District, Sijunjung Regency, West Sumatra. The research method used is the classroom action research method (CAR) which was carried out at SDN 16 Timbulun in the 2019/2020 school year for 25 Class 2 students. The research design used is classroom action research. This research was carried out for two actions (cycles). Each action includes planning, implementation, observation and reflection. Data collection techniques through learning outcomes tests. The results showed that there was an increase in learning outcomes through the use of the problem based learning model for class 2 SDN 16 Timbulun. The results showed that the application of the Problem Based Learning (PBL) learning model can improve the learning outcomes of grade 2 students starting from pre-action, cycle I and cycle II, namely 69.65 in the pre-action stage increased to 79.65 in the first cycle and again increased to 82 ,86 in cycle II. The conclusion of this study is that the application of the Problem Based Learning (PBL) learning model can improve the learning outcomes of grade 2 students at SDN 16 Timbulun in science subjects.